2015
DOI: 10.1016/j.tube.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA analysis – An established technique in charting the evolution of tuberculosis and leprosy

Abstract: Many tuberculosis and leprosy infections are latent or paucibacillary, suggesting a long time-scale for host and pathogen co-existence. Palaeopathology enables recognition of archaeological cases and PCR detects pathogen ancient DNA (aDNA). Mycobacterium tuberculosis and Mycobacterium leprae cell wall lipids are more stable than aDNA and restrict permeability, thereby possibly aiding long-term persistence of pathogen aDNA. Amplification of aDNA, using specific PCR primers designed for short fragments and linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…New insights into bacteria and archaea constituting past microbiota have been gained notably by analyzing ancient dental calculus microbiota [2–4] and digestive tract microbiota [5]. Furthermore, an expanding knowledge of the evolution of pathogens such as Yersinia pestis [6, 7], Mycobacterium tuberculosis and Mycobacterium leprae [8] and variola [9] helped reconstitute the dynamics of past devastating epidemics caused by these pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New insights into bacteria and archaea constituting past microbiota have been gained notably by analyzing ancient dental calculus microbiota [2–4] and digestive tract microbiota [5]. Furthermore, an expanding knowledge of the evolution of pathogens such as Yersinia pestis [6, 7], Mycobacterium tuberculosis and Mycobacterium leprae [8] and variola [9] helped reconstitute the dynamics of past devastating epidemics caused by these pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies culminated in the reconstitution of the complete genome of ancient strains of Y . pestis in Bronze Age individuals [6] and historical plague pandemic victims [7, 14, 15], Vibrio cholerae [16], Mycobacterium tuberculosis [8], Borrelia burgdorferi [17] and Treponema denticola [18]; and host-associated viruses [19] including smallpox virus from human specimens buried for 300 years [9]. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the possibility of diagnosing tuberculosis in archaeological skeletons by detection of preserved "ancient" DNA (aDNA) of M. tuberculosis has been explored (Donoghue et al, 2015), and unambiguous identifications have been reported with material dating back several hundred years, especially when the latest "nextgeneration" sequencing (NGS) methods are used (Bouwman et al, 2012;Chan et al, 2013;Kay et al, 2015). In this paper, we report on testing a portion of a rib bone from William Braine for the presence of M. tuberculosis aDNA.…”
Section: Introductionmentioning
confidence: 99%
“…Nerlich 1997-ben kevéssé specifikus primereket alkalmazott, ahol 133 bp-os terméket kapott a hsp65 génből, de később bizonyítást nyert, hogy az IS6110 sokkal specifikusabb (Donoghue, 2008;Rault és Drancourt, 2008;Nerlich et al, 1997Nerlich et al, , 2009). Helen Donoghue és munkatársai a 2000-es évek elejétől párhuzamosan kétféle inszerciós szekvenciát vizsgáltak (IS6110 és IS1081) a nagyobb diagnosztikus biztonság érdekében (Donoghue 2008(Donoghue , 2011Donoghue et al, 2005Donoghue et al, , 2015.…”
Section: áBra: a Mycobacterium Tubeculosis Is6110 Inszerciós Szekvencunclassified
“…A tuberkulózis (tbc) az egyik legrégebbi fertőző betegség, a megbetegedések száma napjainkban is nagy méreteket ölt (Ortner, 2003;Gutierrez et al, 2005;Hershkovitz et al, 2008;Donoghue, 2009;Baker et al, 2015;Donoghue et al, 2015;Pálfi et al, 2015). A tuberkulózis pandémiás megjelenésű, a WHO becslései szerint jelenleg a Föld népességének mintegy 30%-a látens Mycobacterium tuberculosis hordozó lehet.…”
Section: öSszefoglalóunclassified